DEVELOPMENT OF CONTRAST-BASED NAHWU TEACHING MATERIALS USING MACROMEDIA FLASH - Keysha Aurellia Az-Zahra; Kristina Imron; Bambang Prasetyo; Dinda Sayyidah 'Afifah; Dwi Indah Fajriyah; Yunisa Isnaini (CV. TOTUS TUUS, 2025)
This study aimed to develop Nahwu teaching materials on the topic of idhafah for tenth-grade students using a contrastive linguistic approach and Macromedia Flash. The materials were derived from the original curriculumbased Arabic textbook used at SMA Muhammadiyah 6 Palembang. Employing the ADDIE model, the research proceeded through the Analysis, Design, and Development stages. Pietro's four-step contrastive analysis method was used to highlight structural differences between Arabic and Indonesian noun phrases. Instruments included expert validation sheets, student feedback questionnaires, and observation notes. Results showed that the developed materials were declared valid by subject matter experts and considered feasible for classroom use. The interactive elements embedded in Macromedia Flash contributed to increased student engagement and comprehension. The findings affirm the potential of integrating contrastive linguistic analysis and interactive media in Arabic grammar instruction.